(untitled) (Psychology Travelogs, 2025)
The article deasls with the analysis of the phenomenon of the affective polarisation of the large social groups of the population in the conditions of information uncertainty. In particular, it is noted that the study of the phenomenon of the value-affective polarisation both in the foreign countries and Ukraine is becoming increasingly relevant in the connection with the situation of the global ideological and political confrontation in today’s turbulent world, which could lead to the extremely undesirable consequences for the whole humanity. It is connected with the emergence of the new information technologies, the Internet, and globalization processes. In the most general terms, the value-affective polarisation of a social group or population of any country can be defined as the phenomenon that arises in the process of dividing the views, opinions, judgements, assessments or worldviews of citizens into the two opposing value poles on issues that are the most important to a particular social community. The value-affective polarisation is one of the most important indicators of the stability or instability of a society. It is also a predictor of its psychological state in the future. The value-affective polarisation is a special socio-psychological phenomenon that occurs only in the democratic countries and depends largely on the mass media and means of mass communication, primarily the state television and relatively independent internet, as well as on the laws in force in the country. They can also reduce the level of such polarisation in the society if the special measures are taken to prevent it. The behaviour of the most people in a society with value-affective polarisation is driven by their feelings of uncertainty, which are largely caused by the conflicting information they receive through the media and means of mass communication. In the unfavourable international situation that has developed in the recent years, such information is often extremely contradictory. In this case, under the conditions of uncertainty, the phenomena arise that cannot be adequately explained on the basis of the traditional ideas about rational human behaviour.